Pengaruh Kepemimpinan Melayani Dan Komunikasi Kerja Terhadap Kinerja Pegawai Melalui Mediasi Motivasi: (Studi Pada Direktorat Jenderal Kerja Sama Asean, Kementerian Luar Negeri) - Kurniawan, Shahrun Saprily (Citizen : Jurnal Ilmiah Multidisiplin Indonesia, 2025)
This study examines the influence of servant leadership and work communication on employee performance, with motivation as a mediating variable. This study was conducted at the Directorate General of ASEAN Cooperation, Ministry of Foreign Affairs. The research sample was 116 State Civil Apparatus (ASN) employees with probability sampling techniques. This study is a quantitative study. The data analysis technique used partial least squares - structural inquiry model (PLS-SEM) including Outer Model test, Inner Model Analysis, and Hypothesis Test. The results of this study indicate that (1) servant leadership has a direct significant effect on employee performance. (2) work communication has a direct significant effect on employee performance. (3) servant leadership has a direct significant effect on motivation. (4) work motivation has a direct significant effect on motivation. (5) motivation has a direct significant effect on employee performance. (6) motivation is able to mediate the effect of servant leadership on employee performance. (7) motivation is able to mediate the effect of work communication on employee performance.